Concrete mix design, quality control and specification - Day, Ken W.; Aldred, James; Hudson, Barry (CRC Press/Taylor & Francis, 2014)
"The transformation in concrete technology predicted in the 3rd edition of Concrete Mix Design, Quality Control and Specification has arrived, making obsolete many currently published codes and official guidance. In response to these changes, Ken Day, James Aldred, and Barry Hudson present the thoroughly revised and updated Fourth Edition of this classic resource. Dr James Aldred represents the research, consulting, and specifying side. He is a Technical Director at AECOM, one of the world's largest engineering firms. Barry Hudson represents the production side. Barry is Director of Competency Center Materials at Heidleberg Cement in charge of concrete design and control for several major ready mix organisations in several countries. There has been a tendency to over-regulate concrete mixes which stifles innovation and effective quality control, often reducing performance. The book discusses the troubling trend towards adding performance requirements to existing prescriptive specifications. Many specifications now require additional criteria added in an attempt to improve durability or other properties. The book addresses head-on the matter of prescription vs performance specification and especially the specification of non-strength related performance such as durability. It also discusses the issues associated with sustainability and the impact of new concrete materials such as ready mixed geopolymer, magnesium oxide and calcium carbonate. If you need to know about producing, designing, controlling or specifying concrete, this is the book for you -- or you could wait a year or two for these concepts to be incorporated in official codes."--